2019
DOI: 10.1108/jpmh-07-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Overthinkers, attention-seekers and wallflowers: peer perceptions of clinical anxiety disorders in adolescence

Abstract: Purpose The purpose of this paper is to investigate peer perceptions and stereotypes towards adolescents with clinical anxiety disorders. Design/methodology/approach The study utilised an exploratory qualitative design, using short vignettes to investigate perceptions of three clinical anxiety disorders (panic disorder, generalised anxiety disorder and social anxiety disorder) and a control scenario, situational stress. Responses were analysed using thematic analysis. Findings The results of the study sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(59 reference statements)
0
5
0
1
Order By: Relevance
“…In the study of age groups, it was found that the A-Lit level was significantly higher in the age group of 18–30 years than in the others, and they gained a higher score in A-Lit. Because the prevalence of anxiety disorders is usually more from late adolescence, the present study is somewhat justified ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of age groups, it was found that the A-Lit level was significantly higher in the age group of 18–30 years than in the others, and they gained a higher score in A-Lit. Because the prevalence of anxiety disorders is usually more from late adolescence, the present study is somewhat justified ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hanlon and Swords (2019) demonstrated how qualitative methods are valuable for exploratory work to develop an understanding of a phenomenon, as well as providing the foundation upon which later quantitative work can be built. In their attempt to address the lack of research into stigmatizing responses to clinical anxiety disorders, particularly in adolescence, the researchers reported on qualitative work with a sample of adolescents that ultimately aimed to generate items for a quantitative measure of stereotypes.…”
Section: Qualitative Approaches Within a Mixed-methods Research Designmentioning
confidence: 99%
“…Instead, the handful of studies which examine anxiety disorder stigma have found that the "weak-not-sick" stereotype (WNS)-that is, a belief that the person's symptoms do not reflect a real medical condition and instead reflect personal weakness-may be particularly salient for anxiety disorders, as outlined in a recent review [38]. These findings have also been supported by limited studies in adolescent samples [39,40]. This is important, as the WNS stereotype and perceptions of blame in particular have been associated with increased discrimination, negative attitudes, and a decreased likelihood of seeking appropriate help for mental illness [41][42][43][44].…”
Section: Weak-not-sick: Mental Illness Stigma and Anxiety Disordersmentioning
confidence: 99%